Muckle–Wells Syndrome in a Child With Recurrent Urticaria - Elena M. Kamaltynova; Iulia P. Chasovskikh; Zinaida A. Maevskaia; Svetlana O. Salugina; Evgenii S. Fedorov; Inna E. Gerbek (Вопросы современной педиатрии)
Cryopyrin associated periodic syndromes (CAPS) are rare monogenic autoinflammatory diseases from the group of hereditary periodic syndromes caused by a regulation defect of inflammatory cytokines, in particular interleukin 1β. They include familial cold autoinflammatory syndrome (FCAS), Muckle–Wells syndrome (MWS), and neonatal-onset multisystem inflammatory disease (CINCA/NOMID). Previously, Muckle–Wells syndrome was considered as a triad of symptoms — urticaria, deafness, and reactive amyloidosis. Today, the spectrum of symptoms is constantly expanding: it includes fever, fatigue, conjunctivitis, arthralgia, arthritis, myalgia, irritability, headache, abdominal pain, mouth ulcers, pericarditis, which involves doctors of different specialties in the diagnostic and treatment process, who are not always familiar with this disease. In Russia, single observations of this disease have been described. We present the clinical case of Muckle–Wells syndrome in a 5-year-old child, whose first symptoms appeared at the age of 2 months. This observation underscores the complexity of diagnosing the syndrome in children.